Fast satellite selection method for multi‐constellation Global Navigation Satellite System under obstacle environments. Issue 9 (1st December 2014) - Peng, Ao; Ou, Gang; Li, Gengmin
Abstract : Satellite selection plays an important role in a multi‐constellation Global Navigation Satellite System (GNSS) receiver. A well selected satellite combination can provide better positioning accuracy and lighter computational load. In this study, typical obstacle environments in urban areas and their effects on satellite selection are discussed. A distribution‐free satellite selecting method is proposed. The main idea of this proposed method is to expand the selected satellite subset sequentially. The performance of the proposed methods is validated and compared with four other methods by simulation in typical scenarios. Simulation results show that the proposed method is suitable for urban GNSS applications.